Early infantile epileptic encephalopathy type 54: clinical and neurophysiological aspects - D. V. I; V. A. Aysina (Эпилепсия и пароксизмальные состояния)
A clinical case of a boy aged 20 months old with early infantile epileptic encephalopathy (EIEE) type 54 due to mutated HNRNPU gene presumably suffering from genetic generalized epilepsy and impaired psychomotor development is described. Exome-wide sequencing was carried out by using NextSeq 500 (Illumina, USA). Video electroencephalographic (VEEG) monitoring was conducted by using NeuroScope NS425 (Biola, Russia). The patient was noted to suffer from neonatal delayed motor development and muscular hypotonia with atypical petit mal epilepsy with regional onset at the occipital-parietal-posterior temporal areas based on VEEG data developed at age of eight months as well as progressive psychoemotional disorders. Ethosuximide and valproic acid administered together were efficient in alleviating EIEE seizures that requires to be further followed up. The data obtained allow to identify a precise etiology of epilepsy and apply a differential approach to administer anti-epileptic agents.